(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. For comprehensive functioning and sustainable development, SMEs need external funding. The financial services market offers many sources of such funding, both traditional and new, that can be either catalysts for the development of small business or ‘debt traps’. At the same time, in Ukraine, traditional funding is not always available for SMEs. This is due to the lack of sufficient collateral and the significant riskiness of SMEs projects, which results in the high interest rates or in the lending refusal. Accordingly, the purpose of the article is to identify existing external funding sources for domestic SMEs, to compare the advantages and disadvantages of each of the alternative types of funding, as well as to search the optimal sources of financing for SMEs, taking into account their availability and cost. Results. The article describes the characteristics of external sources of funding for small and medium-sized enterprises in Ukraine (state and international SME’s support programs, bank credit, financial leasing, crowdfunding, and micro-credit). To achieve this goal, first of all, the activity of SMEs in Ukraine was analyzed, in particular by the sold products volume and investments in comparison with other non-financial corporations. It should be noted that over the analyzed period (2014-2018), the share of SMEs increased significantly by the products sales, while investments in all non-financial corporations remain almost unchanged with a significant prevalence of equity in funding. The structure and dynamics of volumes of bank loans to non-financial corporations depending on their size are examined, and the analysis of the dynamics of interest rates is carried out. As a result, it should be highlighted that the possibilities of bank lending for small and medium enterprises are certainly expanding, however, interest rates remain extremely high. That is why other funding options for small and medium-sized enterprises were considered, and international programs were analyzed in detail. Ultimately, the sources of funding were evaluated according to the following criteria: price, term of financing, flexibility, a limited number of specific conditions, the absence of significant requirements for the borrower, the provision of additional services, and accessibility. Conclusions. It was found out that state and international SME’s support programs are the most acceptable by most criteria, and bank credit, financial leasing, crowdfunding, and micro-credit are inferior to some criteria, in particular, price and over-demanding standards in lending.